2013
DOI: 10.1371/journal.pone.0069210
|View full text |Cite
|
Sign up to set email alerts
|

Alveolarization Genes Modulated by Fetal Tracheal Occlusion in the Rabbit Model for Congenital Diaphragmatic Hernia: A Randomized Study

Abstract: BackgroundThe mechanisms by which tracheal occlusion (TO) improves alveolarization in congenital diaphragmatic hernia (CDH) are incompletely understood. Therefore transcriptional and histological effects of TO on alveolarization were studied in the rabbit model for CDH. The question of the best normalization strategy for gene expression analysis was also addressed.MethodsFetal rabbits were randomized for CDH or sham operation on gestational day 23/31 and for TO or sham operation on day 28/31 resulting in four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
32
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 74 publications
(145 reference statements)
9
32
1
Order By: Relevance
“…All experiments were conducted in agreement with the Guide for the Care and Use of Laboratory Animals of the U.S. National Institutes of Health. Anesthesia and surgical procedures for the creation of CDH and TO have been detailed elsewhere (22,62). Briefly, rabbit fetuses were randomly operated at day 23 (pseudoglandular stage of lung development) for partial diaphragm excision (DH) or thoracotomy (sham DH), and at day 28 (early saccular stage) for tracheal ligation (TO) or tracheal dissection without ligation (sham TO).…”
Section: Human Lung Tissuementioning
confidence: 99%
See 4 more Smart Citations
“…All experiments were conducted in agreement with the Guide for the Care and Use of Laboratory Animals of the U.S. National Institutes of Health. Anesthesia and surgical procedures for the creation of CDH and TO have been detailed elsewhere (22,62). Briefly, rabbit fetuses were randomly operated at day 23 (pseudoglandular stage of lung development) for partial diaphragm excision (DH) or thoracotomy (sham DH), and at day 28 (early saccular stage) for tracheal ligation (TO) or tracheal dissection without ligation (sham TO).…”
Section: Human Lung Tissuementioning
confidence: 99%
“…Due to high fetal losses and the small size of neonatal rabbit lungs, left and right lungs from each pup were differently allocated to postmortem analyses. We previously showed that biological and histological features of lung hypoplasia were also present in the right lung, i.e., contralateral to the hernia (62,63). The right upper lobe was gently expanded with 4% paraformaldehyde under vacuum and stored for 24 h at 4°C in fixative solution.…”
Section: Human Lung Tissuementioning
confidence: 99%
See 3 more Smart Citations